Pengaruh Penggunaan Semen PCC pada Kuat Lentur Perkerasan Kaku dengan Penambahan Serat Kulit Kayu Gelam Pada Campuran Beton - Aditya, Yudha Gempa; Niken D.W.S.B.U, Chatarina; Putra, Sasana (Universitas Lampung, 2021)
The flexural strength of rigid pavement is the dominant parameter that influences the concrete pavement performance. In general, concrete is weak against its flexural tensile strength. One alternative that can be used to increase its flexural tensile strength is by adding artificial fibers and/or natural fibers to the concrete mixture. The purpose of this research is to find the effect of adding gelam bark fibers towards compressive strength, split tensile strength, and flexural strength of concrete using PCC cement. In this study, the concrete mixture was added with various percentages of fiber content i.e. 0,2%; 0,3%; 0,4%; 0,6%. The concrete was tested and compared its value of compressive strength, split tensile strength and flexural strength. The results of this study showed that the most influential use of fiber for concrete pavement was 0,4%. The addition of gelam bark fiber by 0,4% could increase the tensile strength of the concrete mixture aged 28 days and 56 days respectively by 6,95% and 23.72% toward the concrete without fibers. The testing of concrete at 28 days age results the split tensile strength value decreased by 4,2% and the compressive strength test decreased by 4,7%.Keywords: Gelam bark fiber, PCC cement, OPC cement, flexural tensile strength, split tensile strength and compressive strength